Implementasi Metode Concept Mapping Untuk Mewujudkan Minat Belajar Siswa Di MTs Mujahidin Purworejo Kepung Kediri - Makhromi (Universitas Islam Tribakti Lirboyo Kediri, 2020)
This study aims to determine the implementation of the concept mapping method to create student interest in learning at MTs Mujtahidin Purworejo, Kepung Kediri. This research uses descriptive qualitative research method. The results of the study indicate that the learning process is in accordance with the target or uses the concept of mapping such as observing activities, questioning activities, exploring activities, associating activities and communicating activities. The result is that students have an increased interest in learning. This is evidenced by the activeness of asking questions, participating in all learning activities to do all tasks given by the teacher